Duodenal adenoma presenting as duodenojejunal intussusception - Neogi, P.; Misra, A.; Agrawal, R. (Acta Biomedica Atenei Parmensis, 2008)
Enteroenteric intussusceptions are rarely observed in adults. Most of these are associated with tumors. We operated a 25-year old female with suspected stricture in the third part of the duodenum. However during laparotomy, duodenojejunal intussusception was found along with an adenoma in the third part of the duodenum associated with a lax ligament of Treitz. The intussusception was reduced and the parts of the duodenum containing the adenoma were resected, followed by an end-to-end duodenojejunal anastomosis. To the best of our knowledge, this is the first reported case of tubulovillous adenoma in the third part of the duodenum presenting as intussusception in an adult.